TI_GERICHTE 16.2017.12 vom 2. April 2019 , Ipoteca legale provvisoria a garanzia di contributi per spese comuni - TI Tribunale d'appello (2019)
Ipoteca legale provvisoria a garanzia di contributi per spese comuni